The Palgrave Handbook of Race and Ethnic Inequalities in Education 2019
DOI: 10.1007/978-3-319-94724-2_25
|View full text |Cite
|
Sign up to set email alerts
|

Turkey: Silencing Ethnic Inequalities Under a Carpet of Nationalism Shifting Between Secular and Religious Poles

Abstract: This article offers a systematic review of educational and sociological research in Turkey on the relationship between race/ethnicity and educational inequality between 1980 and 2017. A major challenge regarding this research topic is that ethnic differences were a taboo topic in Turkey until recently, so systematic information on ethnic differences is lacking. Still, three research traditions could be distinguished, namely research that focuses on (1) regional differences, (2) language differences and (3) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, lack of adequate integration has opened the door to their collective stigmatisation. Even though Turkey is a multicultural society, it has a mono‐cultural and centralised education system and curriculum that silences ethnic, linguistic and religious differences (Baysu & Agirdag, 2019; Çelik et al, 2017). While the policy pursued at the macro‐national level entrenches the hidden curriculum as a monologism, it pervades a hegemonic control over individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, lack of adequate integration has opened the door to their collective stigmatisation. Even though Turkey is a multicultural society, it has a mono‐cultural and centralised education system and curriculum that silences ethnic, linguistic and religious differences (Baysu & Agirdag, 2019; Çelik et al, 2017). While the policy pursued at the macro‐national level entrenches the hidden curriculum as a monologism, it pervades a hegemonic control over individuals.…”
Section: Resultsmentioning
confidence: 99%
“…spirit of nationalism. Three problems that often trigger conflict are (1) regional differences, (2) language differences, and (3) religious differences (Baysu & Agirdag, 2019;Sen, 2022a). The results of the study show that most students are aware that pluralism is a necessity.…”
Section: Nationalism Education At Lirboyo Islamic Boarding Schoolmentioning
confidence: 86%
“…However, studies conducted in Turkey are limited to topics such as globalization and secularism, as was supported in the study of Ataş et al (2021). Although studies on migration, multiculturalism, bilingualism, and refugees in the curriculum field have been carried out in recent years (Akhan & Yalçın, 2016;Başbay & Bektaş, 2009;Baysu & Ağırdağ, 2019;Cırıt-Karaağaç & Güvenç, 2019;Polat & Kılıç, 2013;Özen & Dağyar, 2020;Özenç & Saat, 2019;Sarier, 2020;Seban & Uyanık, 2016), curriculum studies in which social inequalities are generally discussed have not been able to move away from one-dimensionality. In the study conducted by Sever et al (2019), it was revealed that the specification of research topics in the curriculum field remained ambiguous and limited due to the concern that they overlap with the research interests of other disciplines.…”
Section: Scope Of Curriculum Studiesmentioning
confidence: 99%